The Image of Rodion Raskolnikov in Ivan Shmelev’s Late Stories “Why It Happened” (1944) and “Notes of a Non-Writer” (1949) - Yulya U. Kaskina (Достоевский и мировая культура: Филологический журнал)
The article considers for the first time the image of Raskolnikov in the stories by Ivan Shmelev “Why It Happened” and “Notes of a Non-Writer.” It shows how in these stories the writer, using artistic techniques, names, images and quotations from Dostoevsky’s novels, is largely oriented towards the tradition of the latter’s work. The story “Why It Happened” presents the motif of a dream in which a dialogue with the devil takes place, Ivan Fedorovich Karamazov is mentioned, and the name of Rodion Raskolnikov is pronounced. The author of the articles affirms that the hero of Shmelev’s story — a professor, in his youth a revolutionary-minded student and atheist — has a typological kinship with the hero of Crime and Punishment. The words, voiced in a distorted form by the student’s companion during dinner in a restaurant: “And you, Andel, stole so much? or reproached the old woman, like Raskolkin?” help to comprehend the image of Shmelev’s hero more deeply. It also demonstrates the “independent life” of Rodion Raskolnikov outside of Dostoevsky’s novel. The story “Notes of a non-Writer,” considered the beginning of a larger novel, includes many plots. The key one is about the resurrection of Uncle Vasya, and it is also associated with Dostoevsky’s works. Here, Crime and Punishment is quoted directly. Not only the semantic closeness is important, but also the chronological precision in both narratives. An excerpt from Crime and Punishment about Raskolnikov (“in the second week of Great Lent it was his turn to commune together with the entire barracks”) reminds the narrator of the assassination of Tsar Alexander II on March 1, 1881, at the beginning of Great Lent and the reaction of the people to his uncle, an atheist and revolutionary. In both cases, the marker in determining friends and foes for ordinary people is the faith in God. The uncle returns to the family — comes down from his mezzanine — on Easter. This, in turn, reminds the hero of the chapter “Dream in Cana of Galilee” from The Brothers Karamazov and gives courage. The extremely important quote from Crime and Punishment in “Notes of a Non-Writer” showed the same milestones in the spiritual movement of Rodion Raskolnikov and Uncle Vasya from the mezzanine on the way to resurrection.